1994
DOI: 10.1016/0014-5793(94)00583-4
|View full text |Cite
|
Sign up to set email alerts
|

8‐Hydroxydeoxyguanosine

Abstract: Abstract8-Hydroxydeoxyguanosine (80HDG) is a specific marker of oxidative damage to DNA. We have observed that patients with SLE (systemic lupus erythematosus), have undetectable levels of urinary 8OHDG by HPLC. Further analysis by GC-MS confirmed that levels of 80HDG in SLE urine were lo'-fold lower than in an age-and sex-matched control group. Experiments utilising cultures of SLE and normal lymphocytes exposed to H,O, confirmed the impaired ability of SLE lymphocytes to repair 80HDG. We subsequently observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Thus, increased AST may be related to oxidative stress-driven autoantigenesis in SLE [36]. This includes the oxidative modification of DNA that is detectable in circulating immune complexes of patients with SLE [37]. Thus, oxidized DNA released from the injured liver may serve as a danger signal and trigger of anti-DNA in SLE [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased AST may be related to oxidative stress-driven autoantigenesis in SLE [36]. This includes the oxidative modification of DNA that is detectable in circulating immune complexes of patients with SLE [37]. Thus, oxidized DNA released from the injured liver may serve as a danger signal and trigger of anti-DNA in SLE [38].…”
Section: Discussionmentioning
confidence: 99%
“…36 Autoantigens are created during cell death, typically through enzymatic cleavage, as with Ro, 36,37 or generated by oxidative modification, as for oxidized DNA. 38 Present in circulating immune complexes in patients with SLE, 39 oxidized DNA is also found in necrotic debris, which is more pro-inflammatory than apoptotic debris. 41 Indeed, in lupus-susceptible mice, systemic autoimmune disease is induced by dendritic cells that have captured necrotic but not apoptotic debris.…”
Section: Environmental Sources Of Oxidative Stressmentioning
confidence: 99%
“…High immunogenic potential of 8-hydroxy-2'-deoxyguanosine , the main product of oxidative DNA damage, was demonstrated [3,15]. It was also shown that DNA content of 8-OHdG in lymphocytes from patients with SLE considerably surpassed the corresponding value in healthy individuals [4], while the content of 8-OHdG in DNA of immune complexes in the plasma more that 100-fold surpassed that in nucleus DNA [12]. These facts suggest that oxidative modification of DNA can be a factor of induction of autoimmune process in SLE [4].…”
mentioning
confidence: 86%